Pengaruh Pemberian Makanan Tambahan Bubur Kacang Hijau dan Program Pemerintah (Biskuit) Terhadap Peningkatan Status Gizi Batita di Wilayah Kerja Puskesmas Mokoau dan Puskesmas Benu – Benua Kota Kendari Tahun 2018 - Ningrum, Ertika Sekar; Sunarsih, Sunarsih; Toruntju, Sultan Akbar (Jurnal Gizi Ilmiah, 2018)
Toddlers are one of the groups that are vulnerable to nutritional status problems. Toddler period is a period of rapid growth and development, so it is often termed a golden and critical period. On the other hand, if toddlers at this time do not get food according to their nutritional needs, the golden period will turn into a critical period which will interfere with the toddler's growth and development. Good nutritional status is health status resulting from a balance of intake and needs. Parameters of nutritional status can be done by anthropometric measurements, biochemical examination, and anamnesis nutritional history. This type of research is a quantitative research with a quasi-experimental method. The population in this study were all toddlers who experienced malnutrition and malnutrition, totaling 109. The total sample for the mung bean porridge treatment group was 26 toddlers and the biscuit control sample was 26 toddlers. The results of the paired t-test showed that the P value of 0.000 had the effect of giving mung bean porridge and biscuits to improve the nutritional status of toddlers. The results of the regression test showed that there was a relationship between after treatment and before treatment in the green bean porridge and biscuit group. The results of the independent test showed that there was a difference between body weight and body length before and after treatment for toddlers. It is hoped that the Mokoau Health Center and the Benu-benua Kendari Health Center will be able to use the results of this study as information and consideration in increasing awareness of toddlers with nutritional status problems.